2010
DOI: 10.1152/ajplung.00230.2009
|View full text |Cite
|
Sign up to set email alerts
|

Rac1-mediated NADPH oxidase release of O2 regulates epithelial sodium channel activity in the alveolar epithelium

Abstract: We examine whether alveolar cells can control release of O(2)(-) through regulated NADPH oxidase (NOX) 2 (NOX2) activity to maintain lung fluid homeostasis. Using FACS to purify alveolar epithelial cells, we show that type 1 cells robustly express each of the critical NOX components that catalyze the production of O(2)(-) (NOX2 or gp91(phox), p22(phox), p67(phox), p47(phox), and p40(phox) subunits) as well as Rac1 at substantially higher levels than type 2 cells. Immunohistochemical labeling of lung tissue sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Incubating monolayers in TEMPOL (a ROS scavenger) did reduce I sc , a result suggesting that endogenous ROS may stimulate ENaC activity (49,59). However, even in the presence of TEMPOL, O 2 produced its concentration-dependent effects, albeit at a lower absolute level (Fig.…”
Section: Effects Of O 2 and Corticosteroids On Na Transportmentioning
confidence: 85%
“…Incubating monolayers in TEMPOL (a ROS scavenger) did reduce I sc , a result suggesting that endogenous ROS may stimulate ENaC activity (49,59). However, even in the presence of TEMPOL, O 2 produced its concentration-dependent effects, albeit at a lower absolute level (Fig.…”
Section: Effects Of O 2 and Corticosteroids On Na Transportmentioning
confidence: 85%
“…The potential underlying mechanisms for the negative effects of peroxynitrite include posttranslational modification of vulnerable tyrosine and/or cysteine residues in the channel, although little direct evidence has been obtained to support this (81). The effects of superoxide are most likely due to modulation of NADPH oxidase, and scavengers/inhibitors of superoxide resulted in an acute decrease in channel P o (379). This finding, which suggests that a tonic level of superoxide may be required for sustained channel activity, correlates with studies demonstrating that sustained hypoxia is associated with decreased expression of the three main ENaC subunits (384).…”
Section: Enac In Non-cf-related Lung Diseasementioning
confidence: 99%
“…Shibata et al 8 have established recently that signaling cross-talk between Rac1 and the mineralocorticoid receptor modulates receptor activity and identified Rac1 as a therapeutic target for chronic kidney disease. Silva and Garvin 9 and Takemura et al 10 also recently identified an important role for Rac1 in NaCl-induced superoxide generation in the medullary thick ascending limb 9 and in the alveolar epithelium. 10 Members of the Wiskott-Aldrich syndrome protein (WASP)/WAVE family (N-WASP, WASP, and WAVE1, -2, -3 isoforms) share similar domain structure and activate Arp2/3-mediated actin polymerization, leading to distinct downstream effects.…”
mentioning
confidence: 95%
“…Silva and Garvin 9 and Takemura et al 10 also recently identified an important role for Rac1 in NaCl-induced superoxide generation in the medullary thick ascending limb 9 and in the alveolar epithelium. 10 Members of the Wiskott-Aldrich syndrome protein (WASP)/WAVE family (N-WASP, WASP, and WAVE1, -2, -3 isoforms) share similar domain structure and activate Arp2/3-mediated actin polymerization, leading to distinct downstream effects. N-WASP inducibly binds Arp2/3 in response to Cdc42, whereas WAVE proteins constitutively interact with Arp2/3 and are effectors of Rac1 activity.…”
mentioning
confidence: 95%